2016
DOI: 10.1002/brb3.472
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and transcriptome analyses indicate complex breakdown of axonal transport mechanisms in canine distemper leukoencephalitis

Abstract: Introduction CDV‐DL (Canine distemper virus‐induced demyelinating leukoencephalitis) represents a spontaneously occurring animal model for demyelinating disorders. Axonopathy represents a key pathomechanism in this disease; however, its underlying pathogenesis has not been addressed in detail so far. This study aimed at the characterization of axonal cytoskeletal, transport, and potential regenerative changes with a parallel focus upon Schwann cell remyelination.MethodsImmunohistochemistry of canine cerebellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Therefore, it can be assumed that their immunoreactivity indicates their axonal localization. These findings indicate that the accumulation of lysosomal storage material might influence axonal transport and neurofilament phosphorylation status [75,76,88,89,103]. A disturbance in the kinesin-mediated transport of dynein could also affect dynein distribution, because dynein transport is also partly dependent on kinesin (direct transport) [104].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, it can be assumed that their immunoreactivity indicates their axonal localization. These findings indicate that the accumulation of lysosomal storage material might influence axonal transport and neurofilament phosphorylation status [75,76,88,89,103]. A disturbance in the kinesin-mediated transport of dynein could also affect dynein distribution, because dynein transport is also partly dependent on kinesin (direct transport) [104].…”
Section: Discussionmentioning
confidence: 92%
“…NF phosphorylation also controls the association of NFs with kinesin and dynein, and thereby their own axonal transport [100,101]. Thus, alterations in the amount and distribution of β-APP, pNF, nNF, kinesin, and dynein can be used as surrogate markers for axonal damage and disturbed axonal transport [75,76,88,102,103]. Furthermore, the antibodies are restricted to axons only in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the phosphorylation status of neurofilaments is affected by a combination of NGF and G M1 ganglioside. The changes in the neuronal cytoskeleton might affect axonal transport mechanisms and synaptic plasticity 65,66 . Therefore, the expression of the cytoskeletal motor proteins dynein and kinesin and synaptophysin, a synaptic vesicle glycoprotein was investigated.…”
Section: G M1 and Growth Factors Differentially Affect The Neuronal Cmentioning
confidence: 99%
“…In subacute lesions, there is an occurrence of p75 NTR -positive cells, possibly representing a pre-myelinating stage of Schwann cells [ 24 ]. Nevertheless, only single periaxin-positive cells which are suggestive of manifest Schwann cell remyelination, were detected within few advanced lesions [ 25 ]. Furthermore, it was also shown that following extensive axonal degeneration the axonal expression of GAP43, indicative of axonal regeneration, failed to reach the level of significance in dogs with CDV-DL [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only single periaxin-positive cells which are suggestive of manifest Schwann cell remyelination, were detected within few advanced lesions [ 25 ]. Furthermore, it was also shown that following extensive axonal degeneration the axonal expression of GAP43, indicative of axonal regeneration, failed to reach the level of significance in dogs with CDV-DL [ 25 ]. The up-regulation of ECM molecules, especially of chondroitin sulfate proteoglycans, after CNS injury is known to impair axonal sprouting and inhibit remyelination by oligodendroglial cells [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%